PENGARUH TERAPI SLOW STROK BACK MASSAGE TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI PUSKESMAS MUARA - Jenika Nainggolan; Lenny Lusia Simatupang (PT. Hasba Edukasi Mandiri, 2025)
Background: Hypertension is caused by hardened and stiff blood vessels so that the heart pumps blood more strongly. One non-pharmacological therapy that can be used to reduce hypertension is Slow Stroke Back Massage (SSBM) therapy, a massage action on the back with slow strokes for 10-30 minutes with 12-15 strokes per minute. Objective: to determine the effect of Slow Stroke Back Therapy Massage to reduce blood pressure in hypertensive patients at the Muara Community Health Center. Method: The type of research used by researchers is quantitative research. The method used was experimental with a research design using quasi-experiment. The design used in this research was one group pre test and one group post test design and used the Wilcoxon signed rank test with a total of 10 samples. Results: The results of this study showed that there was a decrease in blood pressure in hypertensive patients at the Muara Community Health Center with a value of sig. (2-tailed) 0,000<0,05 Conclusion: there is a significant effect in providing Slow Strok Back Massage therapy on reducing blood pressure in hypertensive patients where the post-test shows that blood pressure values have decreased.